[PP.07.06] EFFECT OF MOXONIDINE ON THE ALDOSTERONE/RENIN RATIO CALCULATED BY BOTH PLASMA RENIN ACTIVITY AND DIRECT RENIN CONCENTRATION IN HEALTHY MALE VOLUNTEERS. (September 2017) - Ahmed, A.; Gordon, R.D.; Ward, G.; Wolley, M.; Stowasser, M.
Abstract : Objective: The most popular screening test for primary aldosteronism (PA) is the plasma aldosterone/ renin ratio (ARR). Medications, dietary sodium, posture and time of day all affect renin and aldosterone levels, and can result in false negative or positive ARRs if not controlled. Most antihypertensive medications affect the ARR and can interfere with interpretation of results. To our knowledge, no study has been undertaken to evaluate the effects of moxonidine on the ARR. Design and method: Normotensive, non-medicated male volunteers (n = 20) underwent measurement (seated, midmorning) of plasma aldosterone (by HPLC-tandem mass spectrometry), direct renin concentration (DRC), renin activity (PRA), cortisol, electrolytes and creatinine and urinary aldosterone, cortisol, electrolytes and creatinine at baseline, and after one week of moxonidine at 0.2 mg/d and a further five weeks at 0.4 mg/d. Results: Compared with baseline, despite the expected significant falls in both systolic and diastolic blood pressure, levels of plasma aldosterone [median 134 (range 90–535) pmol/L], DRC [20 (10–37) mU/L], PRA [2.2 (1.0–3.8) ng/mL/h] and ARR using either DRC [8.0 (4.4–14.4)] or PRA [73 (36–218)] were not significantly changed after either one [135 (98–550) pmol/L, 20 (11–35) mU/L, 2.0 (1.2–4.1) ng/mL/h, 8.8 (4.2–15.9) and 73 (32–194) respectively] or six weeks 130 (90–500) pmol/L, 22 (8–40) mU/L, 2.1 (1.0–3.2) ng/mL/h, 7.7 (4.3–22.4) and 84 (32–192)] of moxonidine. There were no changes in any urinary measurements. Conclusions: Moxonidine was associated with no significant change in the ARR and may therefore be a good option for maintaining control of hypertension when screening for PA.